The Impact of Government Expenditures, Gross Fixed Capital Formation, and Exports on Indonesia’s Gross Domestic Product - Siregar, Rahel Veronika; Nasution, Armin Rahmansyah (Jurnal Warta Dharmawangsa, 2026)
This study analyzes the short-term and long-term relationship between government spending, gross fixed capital formation (PMTB), and exports to Indonesia's Gross Domestic Product (GDP) for the period 2000-2024 using the Vector Error Correction Model (VECM) model. The results of the study show that in the long term, government expenditure has a positive and significant effect on GDP, PMTB has a negative and significant effect, while exports do not have a significant effect. In the short term, the three independent variables have not been shown to have a significant effect on GDP. The results of the Impulse Response Function (IRF) show that the GDP response to shocks of the three variables fluctuates greatly in the initial period (1-19), then towards a stable near zero, indicating that the impact of the shock is temporary. Forecast Error Variance Decomposition (FEVD) analysis revealed that until the 100th period, the contribution of government expenditure to GDP variance was 5.56%, PMTB was 2.00%, and exports was 0.85%, while 91.58% was explained by the GDP variable itself. The study concludes that government spending is effective in driving long-term economic growth, but physical investment still faces structural challenges, and exports have a limited role in the domestic economy.